Malay magic being an introduction to the folklore and popular religion of the Malay Peninsula - Skeat, Walter William 1866-1953 (Silverfish Malaysian classics, 2018)
In their wild state, a Malay once informed me, these women vampires are exceedingly fond of fish, and once and again may be seen "sitting in crowds on the fishing stakes at the river mouth awaiting an opportunity to steal the fish." However that may be, it seems curiously in keeping with the following charm for "laying" a Langsuir.